PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP PAJAK PENGHASILAN BADAN TERUTANG - -, Qotrunnida; -, Rianto; Mujiani, Sari (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to determine the effect of Capital Structure and Profitability on Corporate Income Tax Payable. The sample used in this study consists of companies listed on the Indonesia Stock Exchange (IDX) that published complete financial reports for the years 2020-2023, with 26 companies selected using purposive sampling. The independent variables in this study are Capital Structure, measured by the Debt to Equity Ratio (DER), and Profitability, measured by the Return on Assets (ROA), while Corporate Income Tax Liability is used as the dependent variable. The results of the study indicate that capital structure does not have a significant effect and has a negative relationship with corporate income tax payable. Profitability has a significant positive effect on corporate income tax payable. These findings have important implications for managerial decision-making and corporate tax policy.